How do I do that in photoshop? : the quickest ways to do the things you want to do, right now! - Kelby, Scott (How Do I Do That.., 2024)
The simplest, easiest, and quickest ways to learn over 250 Photoshop tips, tricks, and techniques! Scott Kelby, the world's #1 best-selling photography technique books author, is back with a totally updated and revised new edition of his bestselling book How Do I Do That In Photoshop? The first edition of this bestselling book presented an entirely new concept in Photoshop books--one that's designed from the ground up to get you straight to whatever it is you need to do in Photoshop right now, get your answer fast, and get you back to editing your images in Photoshop. Thanks to Adobe's incredibly popular Creative Cloud Photography plan, which includes Photoshop and Lightroom, photographers are extending the depth and power of Lightroom by jumping over to Photoshop to do all those things Lightroom just can't do (or Lightroom can do, but in Photoshop, it's faster and easier, or the results are just better). Because Photoshop has so much power and depth, sometimes the things you need are...well...kinda hidden or not really obvious. There will be a lot of times when you need to get something done in Photoshop, and you know Photoshop can do it (because Photoshop can do just about anything), but you have no idea where Adobe hid that feature, or what the "secret handshake" is to do that thing you need now so you can get back to working on your images. That's why this book was created: to quickly get you to the technique, the shortcut, the setting, or exactly the right thing you need to do right now. Here's how it works: When you need to know how to do a particular thing, you turn to the chapter where it would be found (Layers, Printing, Fixing Problems, Special Effects, etc.), find the thing you need to do (it's easy, each page covers just one single topic), and Scott tells you exactly how to do it just like he was sitting there beside you, using the same casual style as if he were telling a friend. That way, you get back to editing your images fast. This isn't a book of theory, full of confusing jargon and detailed multi-step concepts. This is a book on which button to click, which setting to use, and exactly how and when to use it, so you're never "stuck" in Photoshop again. This will be your "go to" book that sits within reach any time you're working in Photoshop, and you are going to love having this type of help right at your fingertips.
Keywords: Adobe Photoshop; Photography : Digital techniques; Image processing : Digital techniques